The Influence of Digital Marketing, Brand Awareness, and Customer Experience on Purchase Decisions Among E-Commerce Consumers in Indonesia - Faridah Faridah (Eastasouth Institute, 2026)
The rapid expansion of e-commerce in Indonesia has intensified competition among online businesses, making it essential to understand the factors that influence consumer purchase decisions. This study examines the effects of digital marketing, brand awareness, and customer experience on purchase decisions among e-commerce consumers in Indonesia. A quantitative research approach was employed using a survey method. Data were collected from 275 respondents who had experience purchasing products through e-commerce platforms and were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The measurement model assessment demonstrated satisfactory reliability and validity, with all constructs meeting the recommended thresholds for factor loadings, composite reliability, Cronbach’s alpha, and average variance extracted. The structural model results revealed that digital marketing has a positive and significant effect on purchase decisions, indicating that effective online promotional activities and consumer engagement strategies enhance purchasing behavior. Brand awareness was also found to positively and significantly influence purchase decisions, suggesting that consumers are more likely to purchase products from brands that are familiar and easily recognized. Furthermore, customer experience exhibited the strongest positive effect on purchase decisions, highlighting the importance of website usability, transaction convenience, service quality, and overall shopping satisfaction in shaping consumer behavior. The model explained 74.3% of the variance in purchase decisions (R² = 0.743), indicating substantial explanatory power. The findings demonstrate that digital marketing, brand awareness, and customer experience are critical determinants of purchase decisions in the Indonesian e-commerce sector. This study contributes to the consumer behavior and digital marketing literature while providing practical implications for e-commerce businesses seeking to improve customer acquisition and sales performance.